Patients' and caregivers' views on conversations and shared decision making in diagnostic testing for Alzheimer's disease: The ABIDE project. Issue 3 (10th May 2017) - Kunneman, Marleen; Pel‐Littel, Ruth; Bouwman, Femke H.; Gillissen, Freek; Schoonenboom, Niki S.M.; Claus, Jules J.; van der Flier, Wiesje M.; Smets, Ellen M.A.
Abstract: Introduction: This study aims to assess patients' and caregivers' views on and experiences with (1) decisions about diagnostic testing for Alzheimer's disease (AD) and (2) receiving test results. Methods: We conducted separate focus groups with patients from three hospitals who underwent diagnostic testing for AD ( N  = 11) and their caregivers ( N  = 11). Audio recordings were transcribed verbatim and analyzed using MaxQDA. Results: Patients and caregivers preferred and perceived active involvement in decision making, but the decision to initiate diagnostic testing seems to be made before the clinician‐patient encounter. Patients and caregivers indicate that decisions are driven by a strong need to explain the patient's symptoms. They missed information on why different diagnostic tests were used, what the results of these tests were, and to what extent these results were (ab)normal. Discussion: The decision‐making process around diagnostic testing for AD and the information provision before and after diagnostic testing could be improved.